Efecto de la administración adecuada de calostro sobre niveles inmunitarios, ganancia de peso e incidencia de diarreas en crías de vaquillas de primer parto - Silva, Mauricio (2025)
The effect of controlled colostrum administration (timing of first intake, volume, and immunological quality) on first-calf cow calves was evaluated. Forty-four first-calf Friesian calves were used. Of these, 21 calves were assigned to the control group: colostrum intake by natural suckling from the mother during the first 24 hours of life, and 23 calves were assigned to the treatment group: 6 L bottle-fed colostrum of excellent immunological quality (>50 mg/ml Ig) during the first 12 hours of life. The calves were then artificially reared for 60 days under a traditional system. Total serum protein (TSP) levels were assessed on days 1, 4, and 8 of life, along with daily weight gain (DWG), the occurrence and severity of diarrhoea, and mortality rate. The treatment group achieved a higher TSP concentration (p<0.05) than the control group (6.28, 6.17, and 5.81 vs. 4.6; 4.6 and 4.6 g/dL, respectively) at the three evaluation times. The DWG for the period was higher (p<0.05) in the treatment group (0.370 g/d) compared to the control group (0.317 g/d). Furthermore, there was a higher incidence (p<0.05) of diarrhoea in the control group than in the treatment group and higher mortality (17.4 vs. 0%, respectively).